ROLE OF FUNCTIONAL SH GROUPS ON THE ACTIVITY EXPRESSION AND CONFORMATION MAINTENANCE OF RANA RIDIBUNDA FROG LIVER ARGINASE (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
After inactivation by ethylenediaminetetraacetic acid (EDTA) the subunits (dimer, monomer) of Rana ridibunda frog’s liver arginase differs by sensitivity towards thiol reagents. Moreover, the particular activation of subunits is also observed at the presence of p-chloromercuribenzoate (p-CMB). It is notable, that p-CMB significantly decreases the activity of reactivated enzyme in the presence of Mn2+ ions, despite the fact that in native extracts the enzyme is not inhibited by the thiol reagent. Here we discussed the effect of p-CMB in the inactivation process not only as a result of SH groups’ modification, but also because of structural changes in native conformation by EDTA and non specific reaction of p-CMB with other functional groups.
Keywords: thiol reagent; dimer; monomer